2019
DOI: 10.3389/fphar.2019.00417
|View full text |Cite
|
Sign up to set email alerts
|

Auranofin, an Anti-rheumatic Gold Drug, Aggravates the Radiation-Induced Acute Intestinal Injury in Mice

Abstract: Pelvic and abdominal radiotherapy plays an important role in eradication of malignant cells; however, it also results in slight intestinal injury. The apoptosis of cells in the intestinal epithelium is a primary pathological factor that initiates radiation-induced intestinal injury. Auranofin, a gold-containing triethylphosphine, was approved for the treatment of rheumatoid arthritis, and its therapeutic application has been expanded to a number of other diseases, such as parasitic infections, neurodegenerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…In the present study, we evaluated the role of COX-2 in association with histopathological changes that occur following intestinal irradiation in mice. Previous studies have revealed that intestinal injury after irradiation can be evaluated based on the number of crypts, length of villi, and the size of crypts [10,11,13,15]. The disappearance of intestinal crypts after radiation exposure occurs within 2 days, and a new intestinal shape appears following the recovery of surviving gastrointestinal stem cells 3 to 4 days after irradiation exposure [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we evaluated the role of COX-2 in association with histopathological changes that occur following intestinal irradiation in mice. Previous studies have revealed that intestinal injury after irradiation can be evaluated based on the number of crypts, length of villi, and the size of crypts [10,11,13,15]. The disappearance of intestinal crypts after radiation exposure occurs within 2 days, and a new intestinal shape appears following the recovery of surviving gastrointestinal stem cells 3 to 4 days after irradiation exposure [16].…”
Section: Discussionmentioning
confidence: 99%
“…The isolated small intestines were fixed in 10% neutral buffered formaldehyde and embedded in paraffin wax to prepare 4-µm-thick jejunal sections for hematoxylin-eosin staining. The regenerating crypts in the jejunal cross-sections were then counted by a previously described microcolony technique [10,11]. The criteria for regenerating crypts is as follow: prominent nucleus, little cytoplasm, lying close together and appearing crowded [12].…”
Section: Jejunal Crypt Assay and Morphological Changesmentioning
confidence: 99%
“…The orally administrated Auranofin, a carbohydrate-containing gold complex, is used as an antirheumatic agent [286]. Its main MOA is the inhibition of cellular redox enzymes, resulting in enhancement of oxidative stress and intrinsic apoptotic death.…”
Section: Glycodrugs Miscellaneamentioning
confidence: 99%
“…The treatment of RA is based on five categories of drugs: analgetic, nonsteroidal anti-inflammatory drugs (NSAIDs), glucocorticoids, non-biological and biological disease-modifying anti-rheumatic drugs (DMARDs) (Piovezana Bossolani et al, 2019). These treatments can only temporarily relieve symptoms and may lead to adverse effects such as cardiac complications, ulcers, gastrointestinal damage, and immunosuppression (Lee, Kim, et al, 2019). The intestinal mucosa barrier is a dynamic system that contributes to the stability of the intestinal environment by regulating the absorption of water, electrolytes and nutrients from the lumen into the circulation, while limiting the passage of harmful luminal substances and microorganisms.…”
mentioning
confidence: 99%